(untitled) (diségno, 2022)
In the Digital Era, among emerging technologies, the Digital Twin (DT) is also experiencing rapid and steady development. The DT is a virtual representation of an object or system, connected to it throughout its life cycle. It is a highly complex computerized model, an exact replica of its physical counterpart. The application possibilities of the Digital Twin in the design of products and their subsequent development are greatly increasing due in part to the possibility it offers to interpret various roles of the entire life cycle of the artifact to which it refers. Research in this field is proceeding with the goal of getting to the point of optimizing the internal design process (from concept generation to material selection, from design verification to manufacturing, from delivery to use, and reaching end-of-life management). Based on these considerations, the article aims to highlight how DT can drive innovation in sustainable and circular economy, supporting companies, entities, and institutions to reduce costs, optimize resource use, and decrease carbon footprint. However, despite their potential, DTs have not been critically examined in sustainability paradigms and their benefit toward promoting the Sustainable Development Goals.